Molecular and pathological investigation of avian reovirus (ARV) in Egypt with the assessment of the genetic variability of field strains compared to vaccine strains - Mosad, Samah M.; Elmahallawy, Ehab Kotb; Alghamdi, Abeer M.; El-Khayat, Fares; El-Khadragy, Manal F.; Ali, Lobna A.; Abdo, Walied (Frontiers in Microbiology, 2023)
Avian orthoreovirus (ARV) is among the important viruses that cause drastic economic losses in the Egyptian poultry industry. Despite regular vaccination of breeder birds, a high prevalence of ARV infection in broilers has been noted in recent years. However, no reports have revealed the genetic and antigenic characteristics of Egyptian field ARV and vaccines used against it. Thus, this study was conducted to detect the molecular nature of emerging ARV strains in broiler chickens suffering from arthritis and tenosynovitis in comparison to vaccine strains. Synovial fluid samples (n = 400) were collected from 40 commercial broiler flocks in the Gharbia governorate, Egypt, and then pooled to obtain 40 samples, which were then used to screen ARV using reverse transcriptase polymerase chain reaction (RT-PCR) with the partial amplification of ARV sigma C gene. The obtained RT-PCR products were then sequenced, and their nucleotide and deduced amino acid sequences were analyzed together with other ARV field and vaccine strains from GenBank. RT-PCR successfully amplified the predicted 940 bp PCR products from all tested samples. The phylogenetic tree revealed that the analyzed ARV strains were clustered into six genotypic clusters and six protein clusters, with high antigenic diversity between the genotypic clusters. Surprisingly, our isolates were genetically different from vaccine strains, which aligned in genotypic cluster I/protein cluster I, while our strains were aligned in genotypic cluster V/protein cluster V. More importantly, our strains were highly divergent from vaccine strains used in Egypt, with 55.09–56.23% diversity. Sequence analysis using BioEdit software revealed high genetic and protein diversity between our isolates and vaccine strains (397/797 nucleotide substitutions and 148-149/265 amino acid substitutions). This high genetic diversity explains the vaccination failure and recurrent circulation of ARV in Egypt. The present data highlight the need to formulate a new effective vaccine from locally isolated ARV strains after a thorough screening of the molecular nature of circulating ARV in Egypt.